2021
DOI: 10.1111/all.14832
|View full text |Cite
|
Sign up to set email alerts
|

CytoBas: Precision component‐resolved diagnostics for allergy using flow cytometric staining of basophils with recombinant allergen tetramers

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…By virtue of polyclonal IgE binding with high‐affinity FcεRI, blood basophils can be a target cell for evaluation of allergen sensitization (Figures 2C and 3B). 83 A recent study from our group demonstrated nearly 100% positive predictive values for the detection of sensitization to bee venom and ryegrass pollen using fluorescent allergen tetramers 84 …”
Section: Future Prospectsmentioning
confidence: 98%
See 3 more Smart Citations
“…By virtue of polyclonal IgE binding with high‐affinity FcεRI, blood basophils can be a target cell for evaluation of allergen sensitization (Figures 2C and 3B). 83 A recent study from our group demonstrated nearly 100% positive predictive values for the detection of sensitization to bee venom and ryegrass pollen using fluorescent allergen tetramers 84 …”
Section: Future Prospectsmentioning
confidence: 98%
“…With clinical flowcytometers currently having 10–12 fluorescent parameters, multiplex detection is possible with 8–10 allergen components in combination with IgE and CD123 as basophil markers. Without the need for basophil activation, 85 cytometric detection of allergen sensitization on blood basophils (CytoBas) can be performed on fresh and frozen PBMC in a standard pathology laboratory 84 …”
Section: Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustained unresponsiveness (SU) to peanut was observed in patients with low basophil activation at baseline and those with a greater than 80% reduction in peanut‐induced basophil activation after OIT, 22 supporting the utility of BAT in predicting and monitoring response to OIT. These new technologies including others using novel gating strategies with optimization of storage and automation of measurements and analysis may enable routine high‐throughput analysis in the future 19,23‐25 …”
Section: Diagnosis and Endotypingmentioning
confidence: 99%